A Single-material-printed, Low-cost design for a Carbon-based fabric strain sensor. (September 2022) - Chen, Xiaobin; Wang, Fei; Shu, Lin; Tao, Xiaoming; Wei, Lei; Xu, Xiangmin; Zeng, Qing; Huang, Guozhi
Graphical abstract: Highlights: Single Material was used to fabricate the sensing and connection parts of the flexible strain sensor with one-step printing. Theoretical model and experiments show that the dimensions of the sensor have a negligible effect on the gauge factor. Novel fabric strain sensor fabricated using a simple manufacturing process exhibited excellent mechanical stability and fatigue life. Good response of the fabric strain sensor for detecting human motion verifies its prospective wearable applications. Abstract: The manufacturing of flexible strain sensors for wearable electronics usually requires different conductive materials for the sensing part and the connection part. This increases the complexity, cost, and performance issues due to the mismatch of the thermo-electro-mechanical properties of the materials. Herein, a new design scheme using a single conductive material is presented for a low-cost mass-producible fabric strain sensor, where a carbon/silicone nanocomposite is screen-printed to make both parts. By exploring the dimension effect and modelling of the conductive tracks, and adopting a large difference of over 100 times in aspect ratio, this research makes the electrical response of the fabric strain sensor depend almost exclusively on the sensing part, while its connection part has a low resistance. The sensor exhibits outstanding performance with a wide working range (60% strain), adequate linearity, long fatigue life (∼50, 000 cycles), and mechanical robustness, rendering it suitable for human body movement detection. Moreover, the manufacturing process is simple and low-cost ($11 per m 2 ). Thus, the new design scheme overcomes the mismatch issue and provides an important reference value for the design of flexible resistive sensors working in a high resistance range, from ∼ 100 KΩ to several MΩ.